Washington View: Must we stay divided over education?. (February 2022) - Ferguson, Maria
Education became a major issue in the 2021 Virginia gubernatorial election, when Democratic candidate Terry McAuliffe and Republican Glenn Youngkin clashed over how much say parents should have in their children's education. Youngkin's victory, fueled in part by parent outrage over school curricula, could lead other candidates to stoke fear and outrage over schools to score political points. Maria Ferguson discusses the power of schools to divide society and considers what lessons schools should take from the COVID-19 crisis .